2015
DOI: 10.1007/s00415-015-7688-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for Alzheimer disease: a decision and cost-effectiveness analysis

Abstract: Alzheimer disease (AD) is characterized by impairments in memory function. Standard AD treatment provides marginal improvements in this domain. Recent reports, however, suggested that deep brain stimulation (DBS) may result in improved memory. Given significant equipment costs and health expenses required for DBS surgery, we determine clinical and economic thresholds required for it to be as effective as standard AD treatment. Literature review yielded annual AD progression probabilities, health-related qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Deep brain stimulation (DBS) has evolved into a well-established therapy for Parkinson’s disease [ 1 ], essential tremor [ 2 ], and dystonia [ 2 ], as well as a therapy for multiple sclerosis [ 3 ], cluster headache [ 4 ], Tourette syndrome [ 5 ], and obsessive-compulsive disorder [ 6 ]. DBS is even being investigated as a surgical intervention for obesity, major depression, and a therapy for restoring memory to patients with Alzheimer disease [ 7 , 8 , 9 , 10 , 11 ]. In addition to the primary symptoms treated by DBS, many groups have investigated its effect on autonomic functions at various target sites in the brain [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) has evolved into a well-established therapy for Parkinson’s disease [ 1 ], essential tremor [ 2 ], and dystonia [ 2 ], as well as a therapy for multiple sclerosis [ 3 ], cluster headache [ 4 ], Tourette syndrome [ 5 ], and obsessive-compulsive disorder [ 6 ]. DBS is even being investigated as a surgical intervention for obesity, major depression, and a therapy for restoring memory to patients with Alzheimer disease [ 7 , 8 , 9 , 10 , 11 ]. In addition to the primary symptoms treated by DBS, many groups have investigated its effect on autonomic functions at various target sites in the brain [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…At a success rate of 20 %, DBS can be considered cost-effective for mild AD at the price of $200K per quality-adjusted life year (QALY), while at success rates of 74 %, that price drops to $50K/ QALY. Above 80 % success rate, DBS is both clinically more effective and more cost-effective than standard treatment (Mirsaeedi-Farahani et al 2015). Indeed, phase I trials of DBS for AD, targeting either the fornix (Laxton et al 2010) or NBM (Kuhn et al 2015), have shown that DBS is safe and well tolerated in AD patients, with promising early data for cognitive improvement.…”
Section: Discussionmentioning
confidence: 96%
“…It is associated with significant costs to the individual and society. A recent cost-effectiveness study found that the clinical and economic thresholds required for DBS to be considered cost-effective for AD are relatively low (Mirsaeedi-Farahani et al 2015). Compared to standard treatment, DBS needs only a success rate of 3 % to overcome effects of potential surgical complications on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A cost-effectiveness study found that the clinical and economic thresholds required for DBS to be considered cost-effective for AD are relatively low. [ 27 ] Compared to standard treatment, DBS needs a success rate of only 3% to overcome effects of potential surgical complications on quality of life. At a success rate of 20%, DBS can be considered cost-effective for mild AD.…”
Section: Discussionmentioning
confidence: 99%